Towards fiscal sustainable practices in Mexico: The quality of municipal tax regulation and tiered tariffs improve income from solid waste management services - Sergio López-Olvera; Juan Carlos Olivo-Escudero; Mauricio Hernández-Marroquín; Fausto Rafael López-Olvera; Yessica Lourdes Vallejo-Rivera; Marco Antonio Rodríguez-Gómez; Pedro Hipólito Rodríguez-Herrero (Waste Management Bulletin)
Solid waste management (SWM) is a fundamental responsibility of local governments, essential for public health and environmental sustainability. Globally, fiscal practices, such as tax regulation and tariff structures, are critical for ensuring effective SWM services and achieving sustainable development goals. In Mexico, municipalities face financial constraints and heavily depend on subsidies rather than robust fiscal frameworks to fund SWM operations. This study analyzed the impact of municipal tax regulation and sustainable taxation practices—specifically differentiated and progressive tariffs—on the income generation capacity of 240 Mexican municipalities. Data from municipal financial reports was extracted from official government websites and analyzed using statistical methods in R, including variance analysis and t-tests. The results demonstrate that municipalities with higher levels of tax regulation achieve significantly greater per capita income from SWM services compared to those with minimal or no regulation. Differentiated tariffs based on socioeconomic status were found to be particularly effective, generating income levels 3.29 times higher than uniform tariffs. In contrast, progressive tariffs based on waste quantity did not significantly enhance revenue generation. These findings challenge assumptions about the universal applicability of progressive tariffs and underscore the importance of tailoring fiscal strategies to local economic and social contexts. This study highlights the need for robust tax regulation and strategic fiscal policies to strengthen municipal revenue streams and improve SWM service delivery. It provides valuable information about the impact of tax regulation quality and sustainable fiscal practices on municipal income generation, offering insights for policymakers aiming to achieve fiscal sustainability and equitable access to SWM services.